2022
DOI: 10.1016/j.ejpn.2022.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Acute-onset paralytic strabismus in toddlers is important to consider as a potential early sign of late-infantile Metachromatic Leukodystrophy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Thus, we could substantiate our earlier findings that in late‐infantile MLD MRI abnormalities gradually evolve after symptom onset while in juvenile MLD MRI abnormalities are already present at symptom onset, in a larger cohort and describe early signs in more detail 14 . Part of the present cohort was previously published 4,6,7,14–16,20,25–32 . Fumagalli et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, we could substantiate our earlier findings that in late‐infantile MLD MRI abnormalities gradually evolve after symptom onset while in juvenile MLD MRI abnormalities are already present at symptom onset, in a larger cohort and describe early signs in more detail 14 . Part of the present cohort was previously published 4,6,7,14–16,20,25–32 . Fumagalli et al.…”
Section: Discussionsupporting
confidence: 90%
“…These three early-juvenile outliers might therefore be considered as borderline lateinfantile patients, because of their unusually early age at onset, PNS dominant phenotype, and mild MRI abnormalities. 25 The variation in time before onset as well as the relatively low number of pre-symptomatic patients did not allow us to make statements about typical characteristics of pre-symptomatic MRIs. In spite of these limitations, the scans in pre-symptomatic patients certainly confirmed that in early-onset MLD the largest proportion of the MLD MRI score can be attributed to affected parietooccipital WM, whereas in late-onset patients there is a frontal predominance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While findings from this study do further validate the most common early signs and symptoms of MLD as reported in similar studies [ 3 , 16 , 18 , 25 ], its most distinct contribution is the added color on the specific language used by caregivers to describe these symptoms. This language in combination with the common early physical and cognitive signs can prove a useful resource in recognizing the clues that should trigger a workup for MLD (Table 7 ).…”
Section: Discussionsupporting
confidence: 86%
“…This study provides detailed insights into the initial signs and symptoms of MLD in the words of the caregiver which might trigger suspicion of disease for health care providers. There are few studies that focus specifically on the language used by caregivers of children with MLD—a key information source and important clue for clinicians to address individuals’ symptoms in a timely manner [ 15 – 18 ]. These first signs and symptoms are often missed during the critical window for early therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%